Positive surface charge of GluN1 N-terminus mediates the direct interaction with EphB2 and NMDAR mobility - Halley R. Washburn (Nature Portfolio, 2020)
NMDA receptors undergo constant cycling into and out of the postsynaptic density. Here authors show that NMDAR's GluN1 subunit is required to maintain NMDARs at dendritic spine synapses by direct extracellular interaction with the receptor tyrosine kinase EphB2.